The Political Economy of Child Labor - Ralitza Dimova (Global Labor Organization (GLO), 2021)
Concerns about the welfare of working children has over time produced a wide range of international and national interventions in the child labor market, culminating most recently in a commitment to eradicate the worst forms of child work via the attainment of target 8.7 of the Sustainable Development Goals. While the literature on the causes and consequences of child labor is voluminous and well established, research that explores the political economy of such interventions is disproportionately scanter. This chapter puts the relatively less prolific literature on the political economy of child labor under conceptual and empirical scrutiny. It starts by looking briefly into the theoretical case for interventions into the child labor market and then verifies whether such interventions are justified in practice. It then presents two types of political economy explanations of potential mismatches between economic theory and practice, one in the domain of international interventions and a second one in the realm of national policy making.
Keywords: P48; O14; O15; J13; J24; 330; political economy; child labor; education; minimum age of work; compulsory education